Worse Sleep Quality Aggravates the Motor and Non-Motor Symptoms in Parkinson's Disease - Yi, Qu; Yu-Peng, Chen; Jiang-Ting, Li; Jing-Yi, Li; Qi-Xiong, Qin; Dan-Lei, Wang; Jing-Wei, Zhao; Zhi-Juan, Mao; Yong-Jie, Xiong; Zhe, Min; Zheng, Xue (Frontiers in Aging Neuroscience, 2022)
Backgrounds Sleep disorders are the most common and disabling symptoms in patients with Parkinson's disease (PD). Understanding the associations between sleep characteristics and motor and non-motor symptoms (NMSs) in PD can provide evidence to guide therapeutic interventions and nursing strategies. We aimed to investigate the association between sleep characteristics and motor function and NMSs in PD using multiple approaches. Methods A total of 328 participants were included, and all participants underwent Pittsburgh Sleep Quality Index (PSQI) evaluation and clinical assessments of PD symptoms. We conducted Spearman's correlation to evaluate the associations between sleep and PD symptoms, nonlinear regression to assess the relationships between sleep habits and PD, and mediated analyses to test the effects of NMSs on global PSQI and PD severity, quality of life, and motor symptoms. Results Poor sleep was associated with more severe PD symptoms. In addition, the reflection point for bedtime was around 21:52, associated with motor symptoms, and insufficient and excessive total time spent in bed and nocturnal sleep duration were correlated with higher NMS burdens. The optimal points were 8–9.2 and 6.2–6.9 h, respectively. It was also discovered that NMSs played the mediating roles in global sleep with the quality of life, PD stages, and motor symptoms to a varying range of 6.8–95.4%. Conclusions Sleep disorders have a significant effect on the burden of PD symptoms. The current findings provide new insights into the monitoring and management of sleep and PD and need to be further explored in the future studies.